Promoting Private Sector Development in China: The Challenge of Building Institutional Capacity at the Local Level. (February 2013) - Atherton, Andrew; Smallbone, David
China's rapid growth in recent decades can be attributed in large part to the emergence of a vibrant private sector, which now accounts for around three quarters of the economy. Despite government pronouncements in support of private small businesses, public policy and institutions to support private sector development have been slow to emerge and address their needs. However, many privately owned enterprises are in need of assistance, affected by internal capability constraints such as a lack of management and leadership skills and by an external environment that still privileges state-owned enterprises. Although policy makers may have had other policy priorities in the past, and private enterprises have been able to survive and grow without inputs of professional advice and support, we argue that in the future small and medium-sized enterprises in China will require appropriate and effective business support to continue to grow. In this context we consider two interventions designed to build institutional capacity to provide business support at a local level and the barriers to be overcome if an effective framework for state promotion of privately owned small businesses is to be established.